2021
DOI: 10.3233/wor-213577
|View full text |Cite
|
Sign up to set email alerts
|

Addressing psychosocial work-related stress interventions: A systematic review

Abstract: BACKGROUND: Work-related stress can be defined as an individual’s reactions to work characteristics and indicates a poor relationship between coping abilities and work environment. If unmanaged, stress can impact mental and physical health (e.g., causing depression and cardiovascular disease). Many individuals use maladaptive stress-coping strategies, such as sedentary activities, unhealthy eating behaviors, and alcohol consumption, which do not contribute to long-term stress management. In contrast, stress re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
0
20
0
4
Order By: Relevance
“…In general, these results are consistent with those observed in the literature. In terms of workplace mental health intervention, this trial specifically examined the effects on mental health literacy apart from burnout and stress which are common mental health outcomes of workplace programs ( 35 , 36 ). Randomized Control Trials that focus on multiple aspects, including mental health wellbeing, cognitive understanding, and attitudes toward mental health, are not widely found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these results are consistent with those observed in the literature. In terms of workplace mental health intervention, this trial specifically examined the effects on mental health literacy apart from burnout and stress which are common mental health outcomes of workplace programs ( 35 , 36 ). Randomized Control Trials that focus on multiple aspects, including mental health wellbeing, cognitive understanding, and attitudes toward mental health, are not widely found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Amantea et al [ 11 ], for example, have pointed out that on the issue of vaccinations and doctors’ responsibilities in the 27 countries of the European Community there are very similar criminal and civil responsibilities; therefore, in the detection of this homogeneity, it appears that it would also be desirable to have a similar condition with regard to the obligations, duties, and responsibilities of the occupational physician in relation to checks for alcohol-related conditions. Furthermore, in a study on the medical liability of vaccinations conducted by Beccia et al [ 12 ], it was noted that medical liability is mainly based on Civil Law, since in their study seven out of eighteen countries were based on Common Law; a more uniform behavior in the European Community should be sought for the medical liability of alcohol controls, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found a significant correlation between workplace stress and high levels of alcohol consumption [ 11 , 12 , 13 ]. Alcohol use has been shown to increase the risk of unemployment and, for those employed, absenteeism [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of current interventions is to adjust the worker to the stressful work environment by focusing on individual change [33]. Individual-focused measures are effective [32,34], however, the dramatic increase in absence rates due to mental health problems indicates that overall this is not the solution to keep a sustainable workforce [35]. The majority of work-related stressors in office work are the result of inadequately designed work organisation and management [21], such as interruptions and multi-tasking demands.…”
Section: Introductionmentioning
confidence: 99%